Multifactor Analysis of Calibration and Service Quality of the Soil Moisture Sensor Applied in Subgrade Engineering - Ke Xiao; Wen-qi Bai; Si-si Wang (Advances in Materials Science and Engineering)
The soil is an important natural resource, and its moisture status plays a key role in the strength and stability of the soil structure. In civil industries including the agriculture engineering and the forestry engineering, moisture sensors are widely used to test and monitor the engineering properties and long-term service performance of soil. The influence of multiple factors on the quality and the accuracy of the soil moisture sensor should be taken into account. Both laboratory and field tests were performed by the time-domain reflectometry (TDR) method. The soil dielectric constant and magnetic permeability under different moisture contents, different temperatures, and different dry densities were comprehensively evaluated. At the same time, the sensitive factors in the service performance of the TDR sensor have been revealed by the real state of tested soil samples. Based on the testing principle of TDR, a calibration calculation model has been developed to evaluate accurately the moisture content of the subgrade slope. The results show that both the moisture content and the dry density had a significant influence on the dielectric constant and the magnetic permeability of soil. The developed calculation model has a good fitting effect and stability. Through the model, the influence of moisture content and temperature on the soil dielectric constant has been analyzed, and the fitting goodness is above 90%. After half a year of settlement, the soil was gradually drained and consolidated, and the moisture content of the subgrade section gradually decreased. It verified that the monitoring method determined by the laboratory calibration test was effective and accurate.